Inflammation and chemerin in colorectal cancer - Erdogan, Serpil; Yilmaz, Fatma Meric; Yazici, Ozan; Yozgat, Ahmet; Sezer, Sevilay; Ozdemir, Nuriye; Uysal, Sema; Purnak, Tugrul; Sendur, Mehmet Ali; Ozaslan, Ersan (Tumor biology, 2016)
Chemerin is expressed mainly in the adipose tissue. It is an agonist of chemokine-like receptor-1, which is expressed by the immune system cells. Chemerin stimulates the chemotaxis of the immune system cells, and this indicates the function of chemerin and chemokine-like receptor-1 in the immune response. The tumor microenvironment is very important for determining cancer cell growth and spreading. Therefore, we aimed to investigate the association between colorectal cancer, inflammation, and adipokines including chemerin, adiponectin, and vaspin. The study group consisted of patients with colon cancer, whereas the control subjects consisted of patients with benign conditions, diagnosed with colonoscopy. The two groups were compared in terms of the C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), fibrinogen, adiponectin, chemerin, and vaspin. A total of 41 (28 men, 13 women) patients with confirmed colon cancer, and 27 (15 men, 12 women) controls without, confirmed by colonoscopy, were enrolled. The median chemerin levels were found significantly higher in the study group than the controls (390 vs. 340 ng/mL, p = 0.032), whereas the mean vaspin and adiponectin levels were not significantly different. The median values for the CRP, fibrinogen, and ESR were significantly higher in the patients with colon cancer, when compared to the control group (6.08 vs. 1.4 mg/L, p < 0.0001; 408 vs. 359 mg/dL, p = 0.002; and 30 vs. 8 mm/h, p < 0.0001, respectively). Our results show that higher levels of circulating chemerin, CRP, fibrinogen, and ESR are associated with an increased risk of developing colorectal cancer.